Building (Amendment) Regulations (Northern Ireland) 2016 : Technical Booklet M (Physical infrastructure for high-speed electronic communications networks) : Consultation Draft.: Technical Booklet M (Physical infrastructure for high-speed electronic communications networks) : Consultation Draft. (2016) - Northern Ireland., Department of Finance
No abstract available